On One Class of Almost Bounded Perturbations of Smooth Restrictions of a Closed Operator - Storozh, O. G.; Shuvar, O. B. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We investigate one class of perturbations of a closed densely-defined operator in a Hilbert space. These perturbations change the domain of definition of the operator. We prove that the perturbed operator S is closed and densely defined. We construct the adjoint operator S*.